2018
DOI: 10.1163/15707563-17000099
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the milk urea nitrogen concentration in Chinese Holstein cows

Abstract: In order to investigate the factors affecting milk urea nitrogen in Chinese Holstein cows, a large commercial dairy farm participated in a 30-month study. In this study, the mean milk urea nitrogen concentration was 11.75 mg/dl. The milk urea nitrogen reached its maximum value on day 90 of lactation for the first parity and the third or higher parities, but it peaked at the end of lactation for the second parity. The milk urea nitrogen of the first parity was lower than that of other parities. The milk urea ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
2
1
0
Order By: Relevance
“…The evaluation of milk protein in relation to MU confirmed a negative regression dependency, which was the strongest in early lactation (r = -0.850; P < 0.001), decreasing in mid lactation (r = -0.819; P < 0.001) and late lactation (r = -0.679; P < 0.001). Our results are consistent with previous studies by Zhang et al (2018), who confirmed the negative dependency between milk protein and MU in dairy cows. Other studies examining this relationship did not find a significant correlation between these parameters (Kananub et al 2018).…”
Section: Discussionsupporting
confidence: 94%
“…The evaluation of milk protein in relation to MU confirmed a negative regression dependency, which was the strongest in early lactation (r = -0.850; P < 0.001), decreasing in mid lactation (r = -0.819; P < 0.001) and late lactation (r = -0.679; P < 0.001). Our results are consistent with previous studies by Zhang et al (2018), who confirmed the negative dependency between milk protein and MU in dairy cows. Other studies examining this relationship did not find a significant correlation between these parameters (Kananub et al 2018).…”
Section: Discussionsupporting
confidence: 94%
“…The most significant exceedance of the norm for MU was observed at the second-third months of lactation (33.46-33.49 mg%). These results coincide with the data of other studies [1,3,12,13], but some authors did not find the connection between the concentration of urea and the stage of lactation, or they detected an increase in the level of urea from the first to the fifth-seventh months [14]. Lactation changes in the level of MU are inverse in relation to the variations in MF and MP, the content of which, starting from the second-third months of lactation, gradually increases to maximum in the last month of lactation.…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, leukocytes and epithelial cells make up the majority of somatic cell types in milk and colostrum. According to Maurer et al [28], the somatic cell count (SCC) of milk is frequently used as a barometer for the well-being and quality of lactating animals, and the urea nitrogen concentration is a measure of urine nitrogen excretion that is connected to dietary crude protein (CP) intake and the ratio of degradable to undegradable protein [29].…”
Section: Discussionmentioning
confidence: 99%